Efek NaOH pada Pembentukan Nano ZnO Metode Hidrotermal - Rahma Fauza; Posman Manurung; Yanti Yulianti (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Hydrothermal methods have been developed for the manufacture of ZnO. This study aims to find out the effects of variation on the chemical composition and structure of nanoZnO, the nanoZnO phase formed and the nanoZnO particle size formed. The NaOH variation used is 1; 2; 3; and 4 grams. The characteristics used are X-Ray Diffactions (XRD) and Scanning Electron Microscopy (SEM). The XRD characterization results show that the diffraction peaks correspond to standard databases and show wurtzite phases with hexagon structures. The results of SEM characterization showed that the mean measurement of ZnO particles and the error value in the 1 gram variation was 67 ± 3 nm, while the 3 gram variation was 76 ± 6 nm.